PROFESSIONALLY ORIENTED HISTORICAL AND PEDAGOGICAL TRAINING FUTURE MUSICIANS-TEACHERS: CONTENT, STRUCTURE, IMPLEMENTATION FEATURES - Nikolaeva, Elena V. (Музыкальное искусство и образование, 2021)
The article presents the system of professionally oriented historical and pedagogical training future musicians-teachers developed by the author. Special attention is paid to its origin and further development. The article reveals the target orientation, holistic conceptual and personality-oriented approaches to determining the content and organization of the educational process. The special importance attached to the development of historical and pedagogical thinking of students is emphasized. The necessity of clearly articulated problems in the presentation of educational material and dialogical forms of communication is substantiated; orientation of students to a three-dimensional analysis of the studied historical phenomenon in intonation, paradigm-pedagogical and civilizational aspects; finding ideas for reflection in historical sources, tracing their genesis and pedagogical interpretation of the expediency of adaptation in relation to solving current problems. It is shown that the guidelines that students can be guided by in their activities are: a clear goal and the necessary tools in the form of ideas about the periodization of the history of music education; about research methods; about the content, structure and methods of historical and pedagogical analysis. The importance of forming a positive emotional and value attitude of students to historical and pedagogical training is noted. An extremely brief description of its content and pyramidal structure, covering all levels of university education, is presented.